Faktor yang Mempengaruhi Keterbatasan Perempuan dalam Mengakses Teknologi Komunikasi dan Informasi - F Anita Herawati; Dyah Ayu Retno Widyastuti; Th Diyah Wulandari; Yonathan Dri Handarkho (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
Growing information based on internet technology is an opportunity for people to do easy activity, although not all of the people can get access to it. In fact, there is a limit internet access for women. It has been reflected among Indonesian and such a developed country like US, most of the internet users are male. In terms of Yogyakarta Special Territory internet user phenomena, only five percent women can access internet among 52 percent total users. The internet user gap among male and female in Yogyakarta are amplified by many reasons. This article focused on the Influences factors of internet access limitation and communication technology’s tools ability among female, the internet use based on gender perspective. Social presence theory is used to crack the research question. The research approach used is qualitative, by focus group discussion to observe the information among target. It is hoped that the research has significant contribution for people to empower women community.